2021
DOI: 10.1002/adpr.202100210
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Applications of Polymer Optical Fiber Fuse

Abstract: This article presents a review of the fuse effect in polymer optical fibers (POFs) and its sensing applications. First, the propagation mechanisms and the characteristics of the POF fuse are discussed, showing that its optical threshold power and propagation velocity are much lower than those of silica fiber fuse. In addition, it is shown that the main unique advantages of the POF fuse are its capability of transmitting optical signal as well as the electrical conductivity of the carbonized oscillatory path cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Surprisingly, in contrast to the parameters of silicon-based fibers, fusing the POF can improve their optical and mechanical properties, as well as thermo-optical properties. According to Leal-Junior et al [63], the sensitivity to temperature change has increased from 0.0014/°C for non-fused POF to 0.0160/°C for fused POF. The fusion of POF has resulted in a tenfold increase in temperature sensitivity.…”
Section: Polymer Fiber Optic Sensorsmentioning
confidence: 99%
“…Surprisingly, in contrast to the parameters of silicon-based fibers, fusing the POF can improve their optical and mechanical properties, as well as thermo-optical properties. According to Leal-Junior et al [63], the sensitivity to temperature change has increased from 0.0014/°C for non-fused POF to 0.0160/°C for fused POF. The fusion of POF has resulted in a tenfold increase in temperature sensitivity.…”
Section: Polymer Fiber Optic Sensorsmentioning
confidence: 99%
“…POFs provide various advantages, including cost-efficient connections, improved safety, high flexibility and the ability to fabricate sensing/monitoring devices. [18][19][20] To date, the technologies investigated for the fusion splicing of POFs have included electric arc splicing and thermal splicing with poly (ether ether ketone) tubes. 21) However, although electric arc splicing has been used to process silica glass fibers, the high temperatures associated with this technique can thermally degrade POFs.…”
mentioning
confidence: 99%
“…Huang et al 8) obtained a temperature sensitivity of 93.1 pm °C−1 at 1570 nm using a 0.16 m long polymethyl methacrylate (PMMA)-based step-index POF. Numata et al 9) reported an extremely high-temperature sensitivity of 49.8 nm °C−1 at 1300 nm using a 1.0 m long perfluorinated (PF) graded-index (GI-) POF, 4,[15][16][17] the propagation loss of which is much lower at telecommunication wavelengths than that of a PMMA-based POF. The performance of the PFGI-POF-based SMS sensors has been significantly enhanced so far, [18][19][20][21][22][23][24] while the modal interference in a partially chlorinated POF has also been reported to be of some use in developing temperature sensors.…”
mentioning
confidence: 99%